2021
DOI: 10.1002/jso.26566
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of soft tissue tumors of the abdominal wall: A retrospective study in a high‐volume sarcoma center

Abstract: Background The aim of the study is to evaluate functional and oncological outcomes of patients undergoing abdominal wall soft tissue tumors (AWSTT) surgery. Methods All consecutive patients that underwent surgery for malignant and intermediate AWSTT from 1999 to 2019 were retrospectively analyzed. Results Ninety‐two patients were identified, 20 (22%) operated on for a desmoid tumor and 72 (78%) for a soft tissue sarcoma (STS). Fifty‐two patients (57%) had in toto resection of the abdominal wall (from the skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is also believed that anatomical barriers limit the spread of these tumors and can be respected when not invaded. Sometimes even en-bloc resections (bone, intra-abdominal organs, inguinal ligament resections) with full-thickness abdominal wall resection cannot ensure clear margins of 1 mm but are not associated with higher local recurrence [ 10 ]. The abdominal defect is managed by direct closure, flaps, or the use of prosthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also believed that anatomical barriers limit the spread of these tumors and can be respected when not invaded. Sometimes even en-bloc resections (bone, intra-abdominal organs, inguinal ligament resections) with full-thickness abdominal wall resection cannot ensure clear margins of 1 mm but are not associated with higher local recurrence [ 10 ]. The abdominal defect is managed by direct closure, flaps, or the use of prosthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Direct closure can be preferred for tumors less than 8 cm. The use of prosthetic mesh is associated with a higher rate of postoperative complications since abdominal wall soft tissue tumor surgery tends to have a high risk of infection by itself [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stojadinovic et al 2 reported a longer median time to recurrence of 10 months in a series of abdominal wall sarcomas with a 5‐year DFS of 75% and a distant metastatic rate of 25%. A recent paper by Neuberg et al 17 described surgical outcomes in patients with DFSP and abdominal wall sarcomas treated at a single centre. They reported outcomes of 72 patients with 5‐year OS and DFS as 84% and 59%, respectively, a local recurrence rate of 10% and a distant metastatic rate of 15% at 40 months.…”
Section: Discussionmentioning
confidence: 99%
“…1,15 We performed a literature review of the soft tissue sarcomas of the abdominal wall and found 50-60% of neoplasms were fibromatosis with adipocytic tumors, smooth muscle tumors, and fibroblastic tumors comprising rest of the share, while tumors displaying skeletal muscle differentiation are exceedingly rare. [15][16][17][18][19][20][21][22][23][24] Due to the scattered nature of the data on abdominal wall sarcomas and the lack of existing systematic analyses of these tumors, it is impossible to exactly specify the percentage of RMS or pleomorphic RMS among these tumors.…”
Section: Literature Review and Case Reportmentioning
confidence: 99%